THE REPRESENTATIVE ECONOMIC AGENT – AN EPISTEMOLOGICAL APPROACH - Pătrașcu (Sandu) Diana – Ramona (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2013)
The representative economic agent is an extensively discussed subject in the literature, in general, in the economic literature, in particular. The complexity of this subject inevitably makes it a point of intersection of several research areas - management, mathematics, computer science. The paper aims to reveal the most relevant ideas expressed, in time, by specialists who tried to capture and describe the representative agent. The theoretical approach, that we assumed, respects a temporal coordinate and allows us to finally formulate some relevant conclusions. The importance of the paper is given by the theoretical work to systematize some remarkable ideas on a subject wich is still in the spotlight - the economic representative agent.